2022
DOI: 10.3390/ph15020215
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Shared Decision-Making in Personalised Medicine: Opening the Debate

Abstract: Surgeons and cancer patients are starting to open the debate on how personalised medicine could use shared decision-making (SDM) to balance the personal and clinical components and thus improve the quality and value of care. Personalised precision medicine (PPM) has traditionally focused on the use of genomic information when prescribing treatments, which are usually pharmaceutical. However, the knowledge base is considerably scarcer in terms of how clinicians can individualise the information they provide pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…At the same time the benefits of Precision/Personalized Medicine and the major obstacles for all stakeholders involved are summarized as well as specific solutions are provided. Knowledge and perception of Medical and Pharmacy students towards Pharmacogenomics and Genetics is also presented [6, 8–10, 22, 27–29, 33, 34, 45, 51, 53–55, 59, 67, 74–77, 81–83, 85–107, 112, 113, 121].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time the benefits of Precision/Personalized Medicine and the major obstacles for all stakeholders involved are summarized as well as specific solutions are provided. Knowledge and perception of Medical and Pharmacy students towards Pharmacogenomics and Genetics is also presented [6, 8–10, 22, 27–29, 33, 34, 45, 51, 53–55, 59, 67, 74–77, 81–83, 85–107, 112, 113, 121].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research on shared decision-making yields conflicting evidence regarding its potential benefits, with some studies suggesting positive associations with patient satisfaction and health outcomes (Bomhof-Roordink et al, 2019; Entwistle, 2004; Entwistle et al, 2012; Josfeld et al, 2021), while others express scepticism about its practical application (Gillman & Ferrer, 2021; Guadalajara et al, 2022; Ozdemir & Finkelstein, 2018). In this study, experimental conditions of shared decision-making were found to be linked to heightened trust, reduced emotional distress, and increased patient agency.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, those in borderline anxiety group reported that ‘not understanding the reasons for the medical team’s care decisions contributed to their distress’ (Blok et al, 2023, p. 26). Such studies suggest that since shared decision-making promotes open communication (Guadalajara et al, 2022), there is an increased patients’ and family caregivers’ participation in the treatment process (Lincoln et al, 2023) and lower treatment anxiety (Blok et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If patients (and their families or community) take over (some) responsibility to self-manage their health, scarce healthcare resources can be invested to treat more complex conditions. The shared decision-making model goes hand in hand with the shift to a more open mindset in healthcare (Guadalajara et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%